Java : how to program early objects - Deitel, Paul J.; Deitel, Harvey M., 1945- (How to program series., 2018)
Presents leading-edge computing technologies using the Deitel signature live-code approach, which demonstrates concepts in hundreds of complete working programs. The 11th Edition presents updated coverage of Java SE 8 and new Java SE 9 capabilities, including JShell, the Java Module System, and other key Java 9 topics.